Correction: Highly selective aluminium-catalysed intramolecular Prins reaction for l-menthol synthesis. Issue 79 (28th August 2015) - Itoh, H.; Maeda, H.; Yamada, S.; Hori, Y.; Mino, T.; Sakamoto, Masami
<x xml:space="preserve">Abstract</x> Correction for 'Highly selective aluminium-catalysed intramolecular Prins reaction for l-menthol synthesis' by H. Itoh et al., RSC Adv., 2014, 4, 61619–61623.